Evolvable Embryonics: 2-in-1 Approach to Self-healing Systems - Benkhelifa, Elhadj; Pipe, Anthony; Tiwari, Ashutosh (Elsevier, 2013)
This paper covers the authors’ recent research in the area of evolutionary design optimisation in electronic application domain (Evolvable Hardware). This will be also presented in the context of biologically inspired systems where Evolvable Hardware is concerned with evolutionary synthesis of self-healing systems and potentially hardware capable of online adaptation to dynamically changing environment. We will also illustrate how EAs can produce novel and unintuitive design solutions, and possibly new design principles. The novelty of this research project addresses this compelling change in the traditional landscape of the associated research disciplines by seeking to provide a novel biologically inspired mechanism to support the design optimisation of self-healing architectures, that is Evolvable-Embryonics.
Keywords: Evolvable Hardware; Self-Healing Systems; Bio-Inpired Systems; Fault Tolerance; Evolutionary Design Opimisation